2019
DOI: 10.1016/j.rmed.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COPD-related outcomes in patients initiating a once daily or twice daily ICS/LABA

Abstract: Background: Use of inhaled corticosteroids and long acting beta agonist (ICS/LABA) combination therapy has been shown to decrease the frequency of exacerbations in patients with chronic obstructive pulmonary disease (COPD). In this population, adherence to treatment is associated with better disease control and lower risk of COPD-related exacerbations in the future. Using a treatment with a more convenient regimen or easier-to-use device could improve patient adherence, improve disease control, decrease the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…In a Greek COPD study, omission of medication was also associated with risk of exacerbations [16]. Furthermore, adherence to inhalers has been found to reduce disease severity and related exacerbations [38][39][40]. In agreement with our findings is also the study by Montes et al who they also used TAI questionnaire for assessing adherence to inhalers, and found that poor adherence was significantly associated with worse CAT score and higher risk for exacerbations [12].…”
Section: Poor Adherence To Inhalerssupporting
confidence: 91%
“…In a Greek COPD study, omission of medication was also associated with risk of exacerbations [16]. Furthermore, adherence to inhalers has been found to reduce disease severity and related exacerbations [38][39][40]. In agreement with our findings is also the study by Montes et al who they also used TAI questionnaire for assessing adherence to inhalers, and found that poor adherence was significantly associated with worse CAT score and higher risk for exacerbations [12].…”
Section: Poor Adherence To Inhalerssupporting
confidence: 91%
“…A retrospective database analysis in the US showed similar results for patients treated with once-daily versus twice-daily ICS/LABA. 26 Patients who initiated treatment with once-daily fluticasone furoate/VI had 9% lower risk of having a COPD-related moderate or severe exacerbation and significantly better adherence (PDC≥80%) than those who initiated treatment with twice-daily BUD/FOR. Despite lower exacerbation risk and better adherence to a once-daily ICS/LABA, there were no statistically significant differences between COPD-related and all-cause costs between groups.…”
Section: Discussionmentioning
confidence: 90%
“…A large observational study showed that FF/Vi was associated with a 14% lower risk of having a COPD-related moderate or severe exacerbation compared to BUD/FOR [ 21 ].…”
Section: Resultsmentioning
confidence: 99%